The construction of integrated production management systems in mining companies based on the experience of the ‘Turów’ brown coal mine (Poland) - R. Kus´ (The Southern African Institute of Mining and Metallurgy, 2003)
The paper presents the comments on the advantages of implementing an integrated system of managing mining exploitation in hard coal mines, as well as the comprehensive integration of information on the process of deposit exploitation with economic data, so as to achieve an optimum technical and economic effects. The principles of constructing the production management system have been presented, thanks to which the management boards are provided with reliable technical and economic information on a mining company via information technology. The strategic direction of a company’s operation may currently be verified according to the external conditions that change over time (the information on the deposit, force majeure events, changing expectations of customers, etc.).